Photovoltaic Measurement Using Microprocessor Logger and Current Sensor - Agung Ananto Rhezal; Setiabudy Rudy (MATEC Web of Conferences, 2018)
Nowdays, energy demand increase every years. Some obstacles stand in the way of energy supply. Some obstacles are energy limitation, climate change and environmental regulation. The change of conventional energy to renewable energy is the future solution. The development of renewable energy is the main priority, based on Indonesian government regulations. The potential of solar energy in Indonesia is very large because it is located in the equator. The research tries to measure solar energy in Indonesia region, it use atmega328p microprocessor logger and INA219 current sensor module. The measurement result is used to determine the photovoltaic stand-alone system performance. Measurement variables are sun irradiance, voltage, current, power, energy and temperature. The research method is measurement comparison between photovoltaic system with maximum power point tracking (MPPT) and without MPPT. Sun irradiation measurement with solar power meter is compared with sun irradiation data from NASA. Performance Ratio of the photovoltaic system with MPPT is better than the photovoltaic system without MPPT, the best photovoltaic system with MPPT Performance Ratio (PR) result is 0.93.